The clinical outcome comparison of ischemic stroke with and without atrial fibrillation - Rizaldy Taslim Pinzon; Fransiscus Buwana (National Scientific Medical Center, 2019)
Background: Atrial fibrillation increases the risk of stroke and is associated with poor stroke outcomes. The primary concern of this study was to compare the clinical outcome of ischemic stroke patients with atrial fibrillation and without atrial fibrillation. Methods: This was a retrospective cohort study using secondary data from electronic medical record and electronic stroke registry of Bethesda Hospital Yogyakarta, Indonesia. The data was collected from 2017-2018. The presence of atrial fibrillation at stroke onset and during the acute phase was confirmed by a standard electrocardiogram. The primary outcomes of the study was in-hospital mortality, disability measured by modified Rankin Scale (mRS), and length of stay. We used SPSS 20 with significance level 0,05. Results: Among 1688 patients with ischemic stroke, 45(2,67%) had atrial fibrillation. 51,11% of patients with AF were males and 82,22% aged above 60 years. The mortality of stroke patients with atrial fibrillation group is eighteen patients (40.0%), thirty seven patients (84.4%) have poor functional outcome (mRS≥2) and have length of stay 6 (0-41) days. Bivariate analysis showed stroke patients with atrial fibrillation group is significantly associated with higher in-hospital mortality (RR: 2.11; 95% CI: 1.09-2.22; p: 0.001), worse disability (RR: 2.09; 95% CI: 1.92-2.32; p: 0.001) and prolonged hospital stay (6 (0-41) vs 4 (0-14), p:0.001) than in stroke patients without atrial fibrillation group. Conclusion: Atrial fibrillation is associated with stroke outcomes. Careful cardiac evaluation and appropriate treatment are needed to improve the poor outcomes in patients with ischemic stroke and atrial fibrillation.